Effect of hypoxia-inducible factors in normal and leukemic stem cell regulation and their potential therapeutic impact. (2nd April 2016) - Rouault-Pierre, Kevin; Hamilton, Ashley; Bonnet, Dominique
ABSTRACT: Introduction : Hypoxia inducible factors (HIF-1α and HIF-2α) are the main mediators of hypoxic responses that operate in both normal and pathological conditions. Recent evidence indicates that HIF-1α and HIF-2α could have overlapping, unique and even sometimes opposing activities in both normal physiology and disease. Despite an increase in our understanding of the different pathways regulated by HIF-1α and HIF-2α, the role played by each factor in HSC maintenance and leukemogenesis is still controversial. Areas covered : This review summarizes our current understanding of HIF-1α and HIF-2α activities and discusses the implications and challenges of using HIF inhibitors therapeutically in blood malignancies. Expert opinion : As HIF inhibitors are currently under clinical evaluation in different cancers, including hematological malignancies, a more thorough understanding of the unique roles performed by HIF-1α and HIF-2α in human neoplasia is warranted.